The Padlet Power: Exposing the Success of Writing Learning in University Non-English Basic Classes - Pipit Ertika Daristin; Sakhi Herwiana; Maskhurin Fajarina; Mukminatus Zuhriyah; Sayid Ma’rifatulloh; Elisa Nurul Laili; M. Syaichul Muchyidin (Attractive : Innovative Education Journal, 2026)
This study seeks to assess the effectiveness of Padlet as a tool for teaching writing in classrooms where English is not the primary language. The research adopts a qualitative case study approach. Data were collected through classroom observations, semi-structured interviews, samples of student writing, and documentation of Padlet usage during writing activities. The findings indicate that Padlet increases student engagement, encourages collaboration, and supports the development of writing skills. The interactive and collaborative features of the platform help students generate ideas, reflect on their writing, and respond to feedback from peers and instructors. In addition, the variety of feedback options available on Padlet allows students to better understand their mistakes and improve their writing through revision. Padlet also provides opportunities for teachers to adapt instruction according to students’ learning needs. These findings highlight the potential of collaborative digital platforms to create more interactive and supportive writing environments, offering practical insights for integrating technology into writing instruction in non-English language classrooms